(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One learning model that can be used to improve teachers’ quality, pedagogic competence, and personality is the Project Based Learning (PjBL) learning model. The development in research carried out the Project Based Learning (PjBL) learning model in collaboration with applying the mobile learning model. The use of project-based learning using mobile applications focuses on optimizing teacher performance. The results of this study are: (1) There is an influence of the PjBL strategy assisted by the Mobile Learning Application on the pedagogical competence of teachers. It shows by the significant p-value <0.05; (2) There is an effect of the PjBL strategy assisted by mobile learning on teacher performance which is shown by the significant p-value <0.05; (3) Shown by the average value of the pedagogic competence of teachers for students who have high and low learning motivation with a significant difference of p-value <0.05; (4) The average value shows teacher performance for students who have high against students with low learning motivation with a significant difference with the p-value <0.05; (5) Shows the significant value, p-value <0.05. Moreover, it also shows the average pedagogical competence of teachers who apply the PjBL strategy assisted by mobile learning to students who have high learning motivation reaches the value of 6.2500. Meanwhile, the average score of students who use the PjBL strategy and have high motivation earns 4.2341; (6) The significant value shows it, p-value <0.05, and the average performance of teachers who have high learning motivation is 64.0787.